Effect of Mobile phone communication messages on participation in agriculture among university unemployed graduates - Verlumun Celestine Gever (Cхід, 2019)
The article analyzes an influence of 412 SMS from Mtn Nigeria agro info Services Added Value that were sent by graduates of universities with agricultural specialties during 2018. The author examined the content of those messages and their effectiveness in decision making by young specialists about their employment in Nigerian agricultural enterprises. For this purpose the author divided all messages into four categories (“evidentiary”, “local”, “descriptive”, “striking”). Of them, “evidentiary” messages were the most effective in communication by encouraging unemployed to make constructive decisions about their employment. Generally, the results of the research demonstrates that the messages sent to mobile phones are effective means in attraction of the qualified specialists to the work in agriculture sector of the county. Apart from historical, sociological component of this research is also important, because unemployment of graduates of universities makes them vulnerable and may influence negatively on the society. It is also important that the research may result in positive changes in certain behavior patterns, because now mobile phone is an effective means of not only communication, but also forming of certain tastes and values. Finally, the results of this research may influence on substantive content for mobile phone users, because they reflect a rather significant multiaspectual effectiveness of the named categories of SMS. Therefore, the most important innovation of the article is an evidence of the influence of mobile communication on important behavior reflexes; given facts and conclusions may be useful and instructive for telecommunication service providers and communications experts, as well as for managers of agricultural enterprises, social workers and researchers on this issue. The most important result of this research is the demonstration that due to the receiving agro-informational hints by unemployed graduates of universities a large part of them found employment, at the same time, those who did not regard this information remained unemployed.